Thermally conductive and electrically insulating alumina-coated graphite/phthalonitrile composites with thermal stabilities - Liu, Xianyuan; Wang, Zilong; Sun, Jinsong; Zhao, Zehua; Zhan, Shuyi; Guo, Ying; Zhou, Heng; Liu, Wenbin; Wang, Jun; Zhao, Tong (Composites science and technology, 2021)
Alumina-coated graphite (Al2O3@graphite) core-shell particles were firstly synthesized by a liquid-phase chemical precipitation with the aid of sodium dodecyl sulfonate (SDS) surfactant using an inorganic precursor, then to fabricate thermally conductive and electrically insulating phthalonitrile composites by a hot-compression method. The obtained composite with 40 wt% Al2O3@graphite exhibited a thermal conductivity of 1.409 W/mK, 6.6 times that of pristine phthalonitrile matrix (0.214 W/mK). And the composites still retained electrical insulation below 20 wt% Al2O3@graphite content. Moreover, excellent thermal stabilities had been observed, compared with the glass transition temperature of pristine phthalonitriles (460 °C), the glass transition temperature of the composites decreased slightly but still high. Additionally, at 20 wt% content, the weight loss temperature (T5 and T10) and the char yield at 1000 °C (Yc1000) were 525 °C, 589 °C and 74.9% which was 8 °C, 14 °C and 3.1% higher than that of pristine phthalonitriles, respectively, which holds potential for use in the high temperature thermal management. [Display omitted]